EFFECT OF GELATIN AS A BINDER ON TURMERIC EXTRACT TABLET FORMULATION - Adi Permadi; Iis Wahyuningsih; Sapto Yuliani; Ibdal Satar; Ratna Wijayatri (Universitas Muhammadiyah Magelang, 2022)
The main components for tablet formulations are the fillers, binders, crushers, thinners and lubricants. Among these components, the binders play a key role on the powder cohesion properties during the formation of tablet granules. In this study, turmeric extract tablets were formulated using 15 g of turmeric extract, 35 g of aerosil, 12.8 g of lactose, 1% magnesium stearate, 200 ml of aquadest and gelatin as a binder. To evaluate the effect of gelatin on the tablet formulation, the gelatin was then prepared in different formulation namely 0.1 g (formulation A), 0.2 g (formulation B) and 0.5 g (formulation C), respectivley. Based on the tablet properties, the turmeric tablet with formulation C met the standard requirements of friability less than 1%, the hardness in the range of 4 -8 kg and disintegration time under 15 minutes.